Study of nature of some defects visible in polarized light in sapphire signle crystals - Tkachenko, V.F.; Dan`ko, A.Ya.; Puzikov, V.M.; Budnikov, A.T.; Lukienko, O.A.; Sidelnikova, N.S.; Adonkin, G.T. (Functional Materials, 2007)
Using the precision technique of triple-crystal X-ray diffractometry, the structure of defect parts has been studied in large-size sapphire crystals grown by the horizontal directed crystallization in reducing gas media. The optical polarization analysis has shown that the conoscopic pattern shape and color spectrum are distorted in that region and optical inhomogeneities are present as a striate structure. In the first case, the responsible defects have been established to be the small-angle dislocation twisting boundaries of the micro-blocks with disorientation angles of 0.2 to 5 angular minutes; in the second one, the macro-blocks with turning angles up to several degrees. Experimental results have been presented making it possible to establish the nature and formation kinetics of the small-angle and large-angle disorientations between the micro- and macro-blocks during the crystal growth and annealing.